Knowledge of Vitamin Use among Elementary School Students in Preventing Stunting: Knowledge of Vitamin Use among Elementary School Students in Preventing Stunting - Setiawan, Muhammad Azdar; Ruslan, Ira Indriasari (POLITEKNIK BINA HUSADA KENDARI, 2025)
Developing countries such as Indonesia face the dual problem of under- and over-nutrition. This occurs not only in urban areas but also in rural areas. Of the malnutrition problems, there is a very important problem, namely stunting. Based on the 2018 Basic Health Research, stunting in Indonesia is prevalent at the age of 0-23 months at 29.9%. The purpose of this activity is to compare the knowledge of children of State Elementary School 17 Baruga about the use of vitamins in preventing stunting. This type of research is a combination of descriptive and comparative with the method used, namely a cohort study observational study approach involving a group of 20 5th grade elementary school students. The sampling technique used was accidental sampling and the data were analysed by descriptive statistics and independent sample T-Test. The results showed a significant difference between the group of children who consumed vitamins and the group of children who did not consume vitamins where the average value of knowledge of children who consumed vitamins was 89.20 while the average group of children without consuming vitamins was 63.10 with the resulting t-statistic value of 10,224 (P-value 0.000). The conclusion of this activity is that there are differences in the knowledge of primary school children about the use of vitamins in preventing stunting.